Immunogenicity of DNA Vaccine against H5N1 Containing Extended Kappa B Site: In Vivo Study in Mice and Chickens - Redkiewicz, Patrycja; Stachyra, Anna; Sawicka, Róz∙a; Bocian, Katarzyna; Góra-Sochacka, Anna; Kosson, Piotr; Sirko, Agnieszka (Frontiers in Immunology, 2017)
Influenza is one of the most important illnesses in the modern world, causing great public health losses each year due to the lack of medication and broadly protective, long-lasting vaccines. The development of highly immunogenic and safe vaccines is currently one of the major problems encountered in efficient influenza prevention. DNA vaccines represent a novel and powerful alternative to the conventional vaccine approaches. To improve the efficacy of the DNA vaccine against influenza H5N1, we inserted three repeated kappa B (κB) motifs, separated by a 5-bp nucleotide spacer, upstream of the cytomegalovirus promoter and downstream of the SV40 late polyadenylation signal. The κB motif is a specific DNA element (10pb-long) recognized by one of the most important transcription factors NFκB. NFκB is present in almost all animal cell types and upon cell stimulation under a variety of pathogenic conditions. NFκB is released from IκB and translocates to the nucleus and binds to κB sites, thereby leading to enhanced transcription and expression of downstream genes. We tested the variants of DNA vaccine with κB sites flanking the antigen expression cassette and without such sites in two animal models: chickens (broilers and layers) and mice (BALB/c). In chickens, the variant with κB sites stimulated stronger humoral response against the target antigen. In mice, the differences in humoral response were less apparent. Instead, it was possible to spot several gene expression differences in the spleens isolated from mice immunized with both variants. The results of our study indicate that modification of the sequence outside of the sequence encoding the antigen might enhance the immune response to the target but understanding the mechanisms responsible for this process requires further analysis.